2012
DOI: 10.2478/v10181-011-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term vaccination of a breeding herd of pigs against PCV2 on reproductive parameters

Abstract: The objective of the study was to evaluate an efficacy of sows vaccination protocols in the herd with serious problems affecting efficacy of reproduction. The study was performed in a large pig herd with about 1200 sows. Before vaccination against PCV2, farrowing rate in this farm was about 65%.Sows, boar and replacement gilts were immunized using Circovac vaccine (Merial, France) according to producer's recommendations. Parameters of production were analyzed since 2007 until 2010 in selected batches of sows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
4
5
0
Order By: Relevance
“…Moreover, piglets from vaccinated sows had higher vitality (in the first three hours of life) than the animals issued from non-vaccinated ones in both reproductive cycles. This finding was subjectively reported in a farm with major reproductive problems, most probably related to PCV2, using the same vaccine than the present study [ 28 ]. Besides, since VI was higher in piglets coming from vaccinated sows, one would expect to have less crushed piglets in that group.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, piglets from vaccinated sows had higher vitality (in the first three hours of life) than the animals issued from non-vaccinated ones in both reproductive cycles. This finding was subjectively reported in a farm with major reproductive problems, most probably related to PCV2, using the same vaccine than the present study [ 28 ]. Besides, since VI was higher in piglets coming from vaccinated sows, one would expect to have less crushed piglets in that group.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, sow vaccination at first cycle was applied at a relatively late time during pregnancy when the litter size is already established; therefore, the potential impact of PCV2 vaccination on litter size was only expected after second cycle vaccination. This effect on reproductive parameters is in line with those observed by Pejsak et al [ 28 ], but in disagreement with the ones reported by Kurmann et al [ 23 ]. The first trial [ 28 ] was conducted in a farm with important reproductive problems (most likely related to PCV2-RD) and sporadic PCV2-SD cases.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The herd history was indicative of PCVADs, with increased piglet mortality and reproductive failure. Interestingly, gilts are recorded to be more prone to PCV2‐induced reproductive failure, as observed in the current episode (Farnham et al., ; Pensaert et al., ; Sharma and Saikumar, ; Pejsak et al., ).…”
Section: Discussionmentioning
confidence: 73%